Strategi Pelibatan Masyarakat Dalam Peningkatan Kualitas Sekolah di MAN 2 Kota Bandung - Aisyah, Ia Siti; Nugraha, Mulyawan Safwandy (LPPPI Publishing, 2024)
This study was conducted with the aim of deeply understanding and analyzing community involvement strategies in efforts to improve the quality of education at MAN 2 Bandung City. Qualitative approach descriptive method. The choice of this method is based on the need to deeply understand the complexity and dynamics of community involvement in the specific context of MAN 2 Bandung City. Data were collected through observation, interviews and documentation related to the community engagement strategy at MAN 2 Bandung City. The findings explain that there are 5 community involvement strategies in improving the quality of education at MAN 2 Bandung City, including intensive two-way communication strategies, community involvement in school program planning, empowerment of community potential as a source of learning, active community participation in school activities, strategic partnerships built by MAN 2 Bandung City with various parties have opened access to resources and expertise that enrich the education process. The strategy developed by MAN 2 Bandung offers a framework that can be adapted and replicated, with careful adjustments to the local context. This research has significant implications in improving the quality of Islamic education. However, this research only relies on what is obtained from the results of interviews and observations so that it lacks application in testing a theory related to community involvement in schools. So further research is needed to test the application of the theory of community involvement in schools.